2022
DOI: 10.23736/s0392-9590.22.04747-2
|View full text |Cite
|
Sign up to set email alerts
|

A prospective multicenter randomized clinical trial comparing endovenous laser ablation, using a 1470 nm diode laser in combination with a Tulip-TipTM fiber versus radiofrequency (Closure FAST™ VNUS®), in the treatment of primary varicose veins

Abstract: Background:The treatment of chronic venous disease, has largely shifted from high ligation and stripping to endovenous thermal ablation (EVTA) techniques, because of its comparable efficacy and lack of invasiveness. This clinical trial aimed to compare the efficacy of two thermal ablation techniques, endovenous laser ablation (EVLA) 1470-nm with Tulip-Tip TM fiber and radiofrequency ablation (RFA) ClosureFastTM using a noninferiority design for occlusion rate (primary outcome). Methods: A prospective multicent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Our results are closely similar to previous studies, the reason for this difference is that the sample size in our study was smaller than in previous studies, so no patients in stages C5 and C6 were recorded. A study by Kempeneers et al found that the proportion of people with CVI after EVLA in stage C0 was 80%, C1 was 6%, C2 was 10%, C3 was 3%, and C4 was 1% [9]. In our study, the proportion of patients in stage C0 was 61%, stage C1 was 29.3%, stage C2 was 7.3%, stage C3 was 2.4%, and no patients were recorded in stage C4 or higher.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Our results are closely similar to previous studies, the reason for this difference is that the sample size in our study was smaller than in previous studies, so no patients in stages C5 and C6 were recorded. A study by Kempeneers et al found that the proportion of people with CVI after EVLA in stage C0 was 80%, C1 was 6%, C2 was 10%, C3 was 3%, and C4 was 1% [9]. In our study, the proportion of patients in stage C0 was 61%, stage C1 was 29.3%, stage C2 was 7.3%, stage C3 was 2.4%, and no patients were recorded in stage C4 or higher.…”
Section: Discussionsupporting
confidence: 48%
“…Research by Özkan et al shows that the proportion of women is 63% and men 27% [8]. Other studies have shown similar results, with Kempeneers et al 66% female and 34% male [9]. The reason for the difference in the higher incidence of the disease in women than men is the variability of female sex hormones during pregnancy [10].…”
Section: Discussionmentioning
confidence: 83%
“…7,8 Recent advances in technology have led to new devices getting into the market both on the laser and radiofrequency sides. Recently, laser fibers with new radial rings, different wavelengths, and thinner bodies were introduced 9,10 while only a limited improvement was recorded in radiofrequency devices. 11,12 F-Care is a promising new endovenous radiofrequency ablation device that enables low perivascular tissue injury as the catheter produces 70°C heat that provokes the coagulation of plasma proteins, resulting in denaturation of the vein wall.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, there are also data suggesting that EVLA can be a more painful experience than RFA, with a higher degree of bruising for the patient 6 using the older laser fibres, although there is recent data to suggest comparable post-operative pain and improved quality of life (QoL) scores using the new 1470 nm laser with Tulip-Tip™ fibre. 7,8 Furthermore, depending on which type of RFA catheter utilized, there may well be a significant anatomical recurrence rate in the shorter term with RFA technology. 9 Despite tumescence use as a heat sink, thermal-related complications such as skin burns, nerve damage and endothermal heat-induced thrombosis do occur with RFA and EVLA.…”
Section: Introductionmentioning
confidence: 99%